Montgomery Meigs Taylor papers - Taylor, Montgomery Meigs, 1869-1952.
Correspondence, journal, notebook, orders to duty, newspaper clippings, photographs, and other papers relating primaraily to Taylor's naval career. Documents Taylor's service as commander in chief of the U.S. Navy Asiatic Fleet, the Japanese expansion into China and the invasion of Shanghai in 1932, and life in East Asia. Correspondents include Charles Francis Adams, Ewing E. Booth, Joseph C. Grew, Herbert Hoover, Nelson T. Johnson, Frank Ross McCoy, William Veazie Pratt, Theodore Roosevelt, William Harrison Standley, and Taylor's brother John R.M. Taylor.
Naval officer and commander-in-chief, Asiatic Fleet.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Adams, Charles Francis, -- 1866-1954 -- Correspondence; Booth, Ewing E., -- 1870-1949 -- Correspondence; Grew, Joseph C. -- 1880-1965 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Johnson, Nelson T. -- 1887-1954 -- Correspondence; McCoy, Frank Ross, -- 1874-1954 -- Correspondence; Pratt, William Veazie, -- 1869-1957 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Standley, William Harrison, -- 1872-1963 -- Correspondence; Taylor, John R. M. -- Correspondence; United States. -- Navy. -- Asiatic Fleet; China -- Foreign relations -- Japan; East Asia -- Social life and customs; Japan -- Foreign relations -- China; Shanghai (China) -- History -- Japanese Invasion, 1932.; Naval officers